Facile synthesis of 3D foam-like CoNiO2 for high-performance sodium ion batteries. (December 2017) - Chang, Ling; Wang, Kai; Zhu, Shasha; Huang, Liangai; He, Zhishun; Chen, Miaomiao; Shao, Haibo; Wang, Jianming
Graphical abstract: 3D foam-like CoNiO2 on Cu foil was synthesized by a low-temperature hydrothermal method with subsequent annealing treatment. In the following figure, the left is the schematic illustration of sodium ion and electron transportation of the CoNiO2 film, and the right is the rate performance comparison of the CoNiO2 film and scraped CoNiO2 powder. Highlights: CoNiO2 film is designed as the anode for sodium ion batteries. Unique 3D foam-like structure is synthesized by a hydrothermal method. The binder-free CoNiO2 electrode exhibits excellent sodium storage performances. Abstract: 3D foam-like CoNiO2 on Cu foil was synthesized by a low-temperature hydrothermal method with subsequent annealing treatment. The structure and composition of the 3D foam-like CoNiO2 have been analyzed by field-emission scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). When employed as anode electrode for sodium ion batteries, the as-prepared CoNiO2 film electrode exhibited a high reversible capacity of 323.7 mAh g −1 after 100 cycles at 0.1 A g −1 . Moreover, the CoNiO2 film electrode delivered an excellent rate capability of 210.3 mAh g −1 at 1.6 A g −1 . It is believed that the remarkable electrochemical performance of the film electrode is attributed to the 3D foam-like structure and binder-free feature, which effectively improve the ionic and electron conductivity of the electrode.